2023
DOI: 10.1101/2023.12.11.571054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subspecies divergence, hybridisation and the spatial environment shape phylosymbiosis in the microbiome of house mice

Susana C. M. Ferreira,
Víctor Hugo Jarquín-Díaz,
Aimara Planillo
et al.

Abstract: Closely related host species share similar symbionts, yet how host genetics and the environment affect symbiont communities at different stages of host genetic divergence remains largely unknown. Similarly, it is unclear whether host-symbiont associations result from or contribute to host divergence.We examined the intestinal community of 619 wild-caught mice from Germany’s European house mouse hybrid zone. Here, hybridisation upon secondary contact reflects divergence and could be traced gradually.Temporal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…We found that neither locality nor year of collection were significant predictors of the microbial composition (Beta diversity), while hybridicity explained a low but significant proportion of the overall microbial compositional variance while adjusting for the spatial effects of locality (Permutational multivariate analysis of variance (PERMANOVA), F = 1.38, df = 1, R 2 = 0.003, P = .047) and geographic distance ( Supplement 2 ). Differences in the microbiome of the subspecies and microbiome disruption in hybrids have been observed previously [ 10 , 11 ]. This finding might reflect the association between bacteria and host genetics [ 12 ].…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…We found that neither locality nor year of collection were significant predictors of the microbial composition (Beta diversity), while hybridicity explained a low but significant proportion of the overall microbial compositional variance while adjusting for the spatial effects of locality (Permutational multivariate analysis of variance (PERMANOVA), F = 1.38, df = 1, R 2 = 0.003, P = .047) and geographic distance ( Supplement 2 ). Differences in the microbiome of the subspecies and microbiome disruption in hybrids have been observed previously [ 10 , 11 ]. This finding might reflect the association between bacteria and host genetics [ 12 ].…”
mentioning
confidence: 54%
“…House mice, with genetically diverse subspecies and microbiome variations [ 5 , 6 ], are a suitable model to investigate the effects of host genetics and bacterial community composition on ARGs. Hybrids between these subspecies show much more extreme high or low infection loads of eukaryotic parasites [ 7 , 8 ] and viruses [ 9 ] as well as the composition of the microbiome [ 10 ] and fungi [ 11 ] than pure subspecies, and are referred to as “transgressive phenotypes.” We studied the European House Mouse Hybrid zone (HMHZ), a semipermeable barrier between Mus musculus musculus and Mus musculus domesticus , to assess the impact of this barrier and hybridization on ARGs through microbiome selection.…”
mentioning
confidence: 99%
“…Previous studies in wild nonhuman primates have also documented associations between parasites and bacteria, which are shaped by host-related and ecological factors [118][119][120] . The role and significance of fungi within the intestinal community remains to be elucidated given the scarcity of studies focusing on this taxonomic group within wildlife guts, but see 35,118 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect is often attributed to changes in host physiology, particularly immune development, but also behavioural and dietary changes. Additionally, the host environment (biotic and abiotic factors) shapes the composition of gut microbiomes, as seen by spatial and temporal heterogeneities [33][34][35] , the effect of diet 36,37 and social interactions 38,39 . Importantly, the environment interacts with host physiology and genetics, and these interactions might change over time and are as such context dependent 40 .…”
Section: Introductionmentioning
confidence: 99%